DAMPAK KEBERADAAN ALFAMART DAN INDOMARET TERHADAP KEBERLANGSUNGAN USAHA MIKRO KECIL MENENGAH DI KOTA PEKANBARU - Latif Abdul Rizki; Iyan Yani Rita; Pailis Armas Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims (1) to analyze the omzet level of micro, small and medium enterprises before and after the existence of Indomaret and Alfamart. (2) Analyzing the growth rate of turnover of micro, small and medium enterprises before and after the existence of Indomaret and Alfamart. (3) Analyzing the number of buyers who came to the micro, small, and medium enterprise stores before and after the existence of Indomaret and Alfamart. (4) Analyze changes in the opening hours of micro, small, and medium business stores before and after the existence of Indomaret and Alfamart. This study uses primary data through distributing questionnaires to ninety respondents spread across the city of Pekanbaru. In this study, a quantitative descriptive analysis tool was used which aims to describe a phenomenon, event, symptom, and incident that occurred factually, systematically, and accurately and a sign test which aims to determine the impact of the effect of the sustainability of micro, small and medium enterprises before and after the existence of Indomaret and Alfamart. The results of the sign test of the ninety respondents studied based on the 5% significance level indicated that the p-value <0.05 meant that there was a significant impact. These results indicate a change in the level of turnover, profit and store opening hours due to the presence of Indomaret and Alfamart around micro, small and medium enterprises.Keywords: Impact, UMKM, Indomaret, Alfamart